(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
I provide a thorough assessment of the pyrolysis technique for making carbon black from waste tires in an environmentally friendly way. It looks at the impact of several major factors—including temperature, the layout of the reactor and the environment for the gas—on the carbon black’s yield and quality. Various methods to better carbon black properties are explained, as well as a comparison of old and new pyrolysis practices. Both environmental and industry considerations are highlighted and advice is included on how to maximize operation performance and help fit this approach into circular economy guidelines